Development of a microscopic platform for real-time monitoring of biomolecular interactions - Sasuga, Yasuhiro; Tani, Tomomi; Hayashi, Masahito; Yamakawa, Hisashi; Ohara, Osamu; Harada, Yoshie

(untitled) (Genome Research, 2006)
We developed a new microscopic platform for the real-time analysis of molecular interactions by combining microbead-tagging techniques with total internal reflection fluorescent microscopy (TIRFM). The optical manipulation of probe microbeads, followed by photo immobilization on a solid surface, enabled us to generate arrays with extremely high density (>100 microbeads in a 25 μm × 25 μm area), and TIRFM made it possible to monitor the binding reactions of fluorescently labeled targets onto probe microbeads without removal of free targets. We demonstrated the high performance of this platform through analyses of interactions between antigen and antibody and between small compounds and proteins. Then, recombinant protein levels in total cellular lysates of Escherichia coli were quantified from the association kinetics using antibody-immobilized microbead arrays, which served as a model for a protein-profiling array. Furthermore, in combination with in vitro synthesis-coupled protein labeling, we could kinematically analyze the interaction of nuclear factor κB (p50) with DNA. These results demonstrated that this platform enabled us to: (1) monitor binding processes of fluorescently labeled targets to multiple probes in real-time without removal of free targets, (2) determine concentrations of free targets only from the association kinetics at an early phase, and (3) greatly reduce the required volume of the target solution, in principle to subnanoliter, for molecular interaction analysis. The unique features of this microbead-based microarray system open the way to explore molecular interactions with a wide range of affinities in extremely small volumes of target solutions, such as extracts from single cells.